UPAYA MENINGKATKAN KEMAMPUAN SISWA DALAM MEMAHAMI PERKALIAN DAN PEMBAGIAN MELALUI MODEL PEMBELAJARAN MAKE A MATCH PADA SISWA KELAS II SEMESTER II SD NEGERI BANDUNGREJO 1 TAHUN PELAJARAN2013/2014 - Sudi Eni (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2014)
From the results of preliminary observations made to the second grade students of SD Negeri Bandungrejo 1 Karanganyar District of Demak, the author feels there are shortcomings in the teaching of Mathematics with the subject matter of multiplication and division number to two angka.Kekurangan in learning mathematics is because teachers have to use learning strategies interesting and challenging student activity. This is evident from the low value of the average grade of only 69.72 and a low level of student mastery of the material, which means 72.00% of the 38 students only 28 students who completed while 10 students have not tuntas.Ketuntasan students in learning based on the value KKM each basic competency. For that need to be improved to make a macth models, the results obtained average value before the improvement of learning is then increased to 73.68 69.72 to 81.58 in the first cycle and the second cycle. Percentage of completeness students also increased, where before it was held instructional improvement, the percentage of completeness only 72.00% then increased to 87.00% in the first cycle and 100% in the second cycle. Model suitable learning including learning models make a match (look for the pair) for student achievement. In carrying out the study make a match teacher should prepare carefully, because if not properly design a lot of time wasted. Keywords: PTK, make a match, multiplication and division